An Analysis of Slang Words Found in Anne Marie’s Song Lyrics - Ovalili, Desak Made Sayang; Sulatra, I Komang; Hikmaharyanti, Putu Desi Anggerina (Institut Pariwisata dan Bisnis Internasional, 2024)
This study aims at finding out the types of slang words found in Anne Marie's song lyrics and to analyze the meaning of those slang words. The data of this study were taken from the song lyrics by Anne Marie. This study chose Anne Marie’s song lyrics as data source because there are many slang words found in song lyrics. This study used the theory proposed by Kipfer and Chapman (2007:8) to classify the types of slang words and the theory proposed by Leech (1981) to analyze the meaning used. This study applied observation method in collecting the data of slang words. Qualitative method was used in analyzing the data. This study used formal and informal methods in presenting the finding. Based on the data analysis, there are 17 data of slang words found in Anne Marie’s song lyrics. Those slang words are classified into primary and secondary slang. The dominant type of slang found was primary slang with 16 data. Based on the theory of types of meaning by Leech (1981), there are two types of meaning exist in those slang words, such as; conceptual meaning and social meaning. Conceptual meaning occurred with 16 data and followed by social meaning with 1 data. Conceptual meaning dominantly appeared in Anne Marie’s Song lyrics.